Sustainability Status Index of Simple Agroforestry of Magersaren (SAM) with RAP-SAS Method - Ningsih, Ratih Hesti; Afandhi, Aminuddin; Prasetya, Arik (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2023)
The simple agroforestry system of the Magersaren in UB Forest is a source of livelihood for the community that has long inhabited the area. Unsustainable management will increase the amount of damage. So, it needs information about the sustainability status of the simple agroforestry system of the magersaren on various dimensions with sustainable attribute criteria. This research was carried out in the UB Forest educational forest located on the slopes of Mount Arjuno, Sumbersari Hamlet, Tawang Argo Village, Karangploso District, Malang Regency. This study aims to analyze the sustainability status of the agroforestry system of the Magersaren in the UB Forest Area. Sustainability status is determined based on a sustainability index formulated through multi-dimensional scaling (MDS) analysis of the RAP-SAS (Rapid Appraisal for Simple Agroforestry System) method. Based on the results of the sustainability status analysis, it shows that the simple agroforestry system in UB Forest is good or very sustainable, in the ecological dimension with an index value of 85.16%, the economic dimension of 79.70% and the socio-institutional dimension of 72.91%. Meanwhile, the management and technology dimension were 66.94% which showed a fairly sustainable status with sensitive attributes owned, namely business planning and processing with an RMS (Root Mean Square) value of 12.3.